Pengembangan Metode Menulis Puisi Menggunakan Teknik “Atafora” untuk Meningkatkan Kepekaan Siswa terhadap Lingkungan - Elvin Nuril Firdaus; Sony Sukmawan (Universitas Mulawarman, 2022)
Writing poetry is a person's creative activity in expressing ideas, feelings, and thoughts in written form with a figurative meaning. Poetry writing activities are included in the competence of learning Indonesian. However, a few SMA Negeri 3 Malang students are interested in writing poetry, especially in class X. In addition, the method of writing poetry taught by the teacher is less innovative, so students are less interested. Based on these problems, this study aims to develop a method of writing poetry